The Multigenerational Impact of Children and Childcare Policies - Sencer Karademir; Jean-William Laliberté; Stefan Staubli (Institute of Labor Economics (IZA), 2023)
The disproportionate impact of children on women's earnings constitutes the primary factor contributing to persistent gender inequality in many countries. This paper examines the multigenerational impact of children and whether the public provision of formal childcare lessens the earnings and employment impacts of children. Our analyses notably incorporate the role of grandparents as informal providers of childcare. We find that the arrival of a firstborn reduces the employment and earnings of mothers and grandmothers, suggesting that the life-cycle impact of children on women is larger than previously thought. Studying the implementation of a universal childcare program in the province of Quebec, we find that formal childcare increases the employment rates of mothers, as well as that of grandmothers to a lesser extent. Examining heterogeneity of the program's impact across census divisions, we find a negative correlation between the magnitude of the positive effects on mothers' employment and the pre-policy supply of informal childcare by grandmothers. Our findings together indicate that (1) analyses of social policies should consider broader family units and (2) the impact of childcare policies on mothers depends on pre-existing care arrangements, particularly the amount of care provided by grandparents.
Keywords: H31; H42; J08; J13; J16; J18; J22; 330; childcare policies; labour supply; grandparents; parents; event study; policy reform